Complex coacervates based on gelatin and sodium carboxymethyl cellulose as carriers for cinnamaldehyde: Effect of gelatin Bloom values on coacervates formation and interfacial properties. (December 2021) - Liu, Bingjie; Lai, Lingfeng; Muhoza, Bertrand; Xia, Shuqin
Abstract: The formation and interfacial property of complex coacervates were characterized based on CMC and gelatin with different Bloom values (140, 180, 200, 220, and 240). Gelatins with higher Bloom values had more α-chains and β-chains as well as more triple-helix structures. The turbidity curve and optimal pH point for electrostatic neutralization between CMC and gelatin were dependent on the Bloom value. The complex coacervate with medium Bloom values (200) and mass ratio (gelatin/CMC 9:1) showed higher yield (87.56%) and more uniform spherical microstructure, which was correlated with appropriate binding sites and steric hindrance of gelatin. The existence of gelatin with the lower Bloom value enhanced the emulsifying activity of complex coacervates by decreasing the interfacial tension to 16.4 mN/m. However, higher Bloom value was beneficial to the emulsifying stability of the complex coacervates with the ESI up to 21.3 min. With the increasing of molecular weight, the stability of the coacervate exhibited an increasing trend for the higher thickness of the interface film. When used gelatin (200, Bloom value) for microencapsulating cinnamaldehyde, the thermal stability improved significantly and core material uniformly released compared with unencapsulated cinnamaldehyde. Graphical abstract: Image 1 Highlights: Influence of gelatin Bloom value on characteristics of coacervates was investigated. Properties of coacervates were analyzed by using physical and chemical method. Gelatin with Bloom value of 200 was more suitable for complex coacervates. The embedding of cinnamaldehyde could be stabilized based on gelatin/CMC coacervates.